Pengaruh Komunikasi Antar Pribadi dan Tingkat Sosial Ekonomi Terhadap Partisipasi Masyarakat Dalam Membayar PBB Di Kecamatan Kota Kudus - Lestari, Mangesti; Sundarso, Sundarso; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Under UU No. 12 In 1985, PBB is a major source of funds contributed to the development of the country, because the people are required to pay to participate in PBB. Participation in this study is still problematic in stages interpersonal communication still often have mis communication and socio- economic communities is problematic on many dependents. The purpose of this study was to determine the effect of interpersonal communication and socio- economic level of people's participation in the PBB pay. While the theory is used in connection with the factors that affect people's participation raised by Tjokroamidjojo, Santoso Sastropoetro, and Slamet. The number of samples in this study was 96, while data analysis is done with quantitative data analysis using explanative type of research, which tests the hypothesis using Kendall Rank. From the data analysis, there was a positive relationship between interpersonal communication against public participation, in which Kendall Rank correlation coefficient of 5.368 with a coefficient determinant of 13.83% and a positive relationship between socio-economic level of people's participation which Kendallnya Rank correlation coefficient for determinant coefficient of 5.757 with 15.92% and there is a positive relationship between interpersonal communication and socio-economic level of people's participation in PBB where the pay is obtained by calculating the chi-square of 101.224 with a determination coefficient of 27.77%. So that the hypothesis is accepted at the 5% significance level. Recommendations made in this fieldwork is that taxpayers are more aware of the obligation to pay the PBB and sanctions must be confirmed delays.